Long-lasting effects of lavender exposure on brain resting-state networks in healthy women - Kupers, Ron; Dousteyssier, Océane; Delforge, Jérôme; Gonnot, Vanessa; Kantono, Kevin; Blerot, Bernard; Pêtre, Arnaud; Dricot, Laurence; Heinecke, Armin (Frontiers in Neuroscience, 2025)
IntroductionMost brain imaging studies on olfaction focus on short-term odorant stimuli, with few examining long-lasting odor exposure or its after-effects. In this study, we utilized resting-state fMRI (rsfMRI) to investigate the effects of prolonged odor exposure to lavender on brain activity and whether these persist post-exposure.MethodsFourteen healthy women underwent two fMRI sessions, conducted one week apart, in a randomized order. Both sessions included rsfMRI scans before, during, and up to 2 h after a 14 min exposure to either lavender essential oil or a non-odorant control.ResultsAn Independent Component Analysis identified the salience network (SAL) and default mode network (DMN) as the most consistent resting-state networks. A two-factorial ANOVA revealed significant time-varying interaction effects between the SAL and DMN. During odor exposure, functional connectivity (FC) increased within the SAL, and a negative correlation between the SAL and DMN appeared, which intensified immediately after exposure. Two hours post-exposure, the FC between SAL and DMN turned positive.DiscussionThese findings suggest that prolonged odorant exposure to lavender can induce long-lasting brain effects detectable up to 2 h afterwards in women. This proof-of-concept study should be extended to other odorants and to men, and offers new possibilities for exploring the effects of aromatherapy or other odor exposure interventions on brain activity.